Electronic cigarette aerosol induces significantly less cytotoxicity than tobacco smoke. (23rd July 2016) - Azzopardi, David; Patel, Kharishma; Jaunky, Tomasz; Santopietro, Simone; Camacho, Oscar M.; McAughey, John; Gaça, Marianna
Abstract: Electronic cigarettes (E-cigarettes) are a potential means of addressing the harm to public health caused by tobacco smoking by offering smokers a less harmful means of receiving nicotine. As e-cigarettes are a relatively new phenomenon, there are limited scientific data on the longer-term health effects of their use. This study describes a robust in vitro method for assessing the cytotoxic response of e-cigarette aerosols that can be effectively compared with conventional cigarette smoke. This was measured using the regulatory accepted Neutral Red Uptake assay modified for air–liquid interface (ALI) exposures. An exposure system, comprising a smoking machine, traditionally used for in vitro tobacco smoke exposure assessments, was adapted for use with e-cigarettes to expose human lung epithelial cells at the ALI. Dosimetric analysis methods using real-time quartz crystal microbalances for mass, and post-exposure chemical analysis for nicotine, were employed to detect/distinguish aerosol dilutions from a reference Kentucky 3R4F cigarette and two commercially available e-cigarettes (Vype eStick and ePen). ePen aerosol induced 97%, 94% and 70% less cytotoxicity than 3R4F cigarette smoke based on matched EC50 values at different dilutions (1:5 vs. 1:153 vol:vol), mass (52.1 vs. 3.1 μg/cm 2 ) and nicotine (0.89 vs. 0.27 μg/cm 2 ), respectively. Test doses where cigarette smoke and e-cigarette aerosol cytotoxicity were observed are comparable with calculated daily doses in consumers. Such experiments could form the basis of a larger package of work including chemical analyses, in vitro toxicology tests and clinical studies, to help assess the safety of current and next generation nicotine and tobacco products.